Urbanisation côtière en Algérie, Processus et impacts sur l’environnement : Le cas de la baie d’Aïn el Turck - Ghodbani Tarik; Semmoud Bouziane (Études Caribéennes)
A few kilometres from Oran, the coastal area of Ain el Turck previously known for its beautiful beaches, has suffered in recent decades uncontrolled urbanization affecting mainly the maritime public domain (DPM). Currently, the upper parts of beaches like St. Roch, Paradis, Trouville, Bouisseville or lined with villas from one to two floors, garages for boats and large hotels. Encroachment on these areas yet protected by several laws, participated in the erosion of the sandbank and the decline of seaside tourism. This reflected a marked difficulty in managing and protecting this fragile and coveted space.Our study of the coastal area of Ain el Turck will address four points: the relationship between 'concretisation' of shoreline and shoreline change, the evolution of urbanization and occupation strategies, types of competition between different users on the ownership of coastal land and finally, the difficulties in protecting the maritime public by managing services.The method of work is essentially based on two approaches:the first is the comparison between several aerial photographs at different dates, for identifying changes affecting the natural shoreline in relation to the evolution of the urbanization of the coast. The second is conducting interviews with stakeholders in the area and analysis of speeches made by various interest groups, often in conflict.